E-Commerce Implementation Towards SME's Achievement - Kristina, Natalia; Gunawan, Erick Teofilus; Memarista, Gesti (Universitas Negeri Makassar, 2023)
Advances in technology and business competition that is quite rapid require that Micro, Small and Medium Enterprises, MSMEs adapt quickly. MSMEs' efforts to survive in these conditions are carried out through the use of e-commerce and fulfillment of customer satisfaction which plays an important role in the financial performance of MSMEs. This study discusses the effect of using e-commerce and customer satisfaction on 157 MSME owners across Indonesia. The method used in this research was carried out by distributing questionnaires filled out by MSME owners which were processed using multiple analysis. The results of this study indicate that the use of e-commerce has a positive effect on financial performance in SMEs and customer satisfaction has no effect on financial performance. This study explains that e-commerce usage by MSMEs is able to optimize performance including increasing sales, reducing costs, increasing profits and increasing the amount of inventory that is taken out. Meanwhile, financial performance is not affected by customer satisfaction from the use of e-commerce, which means that using e-commerce or traditional sales by MSMEs will not affect customer satisfaction. The results of this study conclude that the financial performance of MSMEs can be optimized through e-commerce usage without being affected by customer satisfaction.